Meta-analysis of factors affecting women's deviant behavior - taha ashayeri; asghar vosogiasl; mojtaba shoaa ardabili; Tahereh Jahanparvar (مطالعات اجتماعی روان‌شناختی زنان)
Deviant behavior is an action outside of the custom, norm, law, and codified and uncodified social values that deviates from the established boundaries and customary standards and violates collective rules. Today, the amount of social harm among women has increased, and accordingly, the main purpose of the study is to study the meta-analysis of factors affecting women's deviant behavior. The research method is a systematic review meta-analysis; from the statistical population of 69 studies between 2002 and 2024; 52 articles were selected using snowball sampling based on the inclusion and exclusion criteria and analyzed with cma2 software. The results show that social factors (family disintegration = 0.396r, weak social cohesion = 0.283r, experience of family violence = 0.145r, social supervision = 0.139r, interaction with inappropriate friends = 0.301r); Cultural factors (low religious affiliation r = 0.402, cultural poverty r = 0.308, risky lifestyle r = 0.312, low cultural capital r = 0.176, presence in cyberspace r = 0.225), psychological factors (feeling of failure r = 0.511, feeling of alienation r = 0.143, criminal label r = 0.103, antisocial personality r = 0.111, feeling of worthlessness r = 0.320); economic factors (socio-economic status r = 0.199, poverty r = 0.111,